Optimalisasi Proses Packing di PT. XYZ Melalui Identifikasi dan Analisis Downtime - Enda; Agus Suwarno; Supriyati Supriyati (Universitas Islam Raden Rahmat, Malang, 2024)
PT. XYZ is a manufacturing company that operates in the field of making motorbikes, the production process is divided into two departments or parts, namely assembly and packaging. However, problems often occur in companies, namely related to fulfilling consumer demand, in the form of targets not being achieved, this occurs because of the high value of downtime in the production process. The aim of this research is to identify and analyze activities that cause downtime in the production process. This research uses qualitative-quantitative methods. The research results show that there are six activities that are indicated to be the main causes of downtime in the packing process, with the highest values being material supply activities and communication with foreman between production activities, reaching 78% of the total downtime. Several recommendations for improvements proposed from the research results include efficiency of material supply methods, communication arrangements, creation of operational process maps, implementation of the FIFO system, and improvements to layout on conveyors.